Toxicity effects of Eriocephalus africanus L. leaf essential oil against some molecularly identified phytopathogenic bacterial strains. Issue 23 (1st December 2020) - Behiry, Said I.; EL-Hefny, Mervat; Salem, Mohamed Z. M.
Abstract: Essential oil (EO) from Eriocephalus africanus L. leaves was evaluated against the growth of some phytopathogenic bacteria including Agrobacerium tumifaciens, Dickeya solani, Erwinia amylovora, Pseudomonas cichorii and Serratia pulmithica using the disc diffusion method and minimum inhibitory concentration (MIC) evaluation. Ten compounds in the EO with dominance of Artemisia ketone (2, 5, 5-trimethyl-2, 6-heptadien-4-one) (77.92%) and ledol (19.92%) were revealed. The antibacterial activity indicated efficacy of essential oil against majority of strains isolated. The most effective action was recorded against D. solani, by 7.5 and 10 µL of oil, with 18.33 mm and 100 μg/mL as zone inhibition and MIC, respectively, whereas the lowest activity was exhibited against P. cichorii (diameter inhibition = 6.66 mm at 10 µL of oil, MIC = 100 μg/mL). The strain S. pulmithica appears to be resistant to the oil when the activity is measured by 10 µL of oil but its growth inhibition was reported with a MIC of 100 μg/mL. Graphical Abstract: